Efecto antibacteriano in vitro del extracto hidroetanólico de la semilla de Persea americana frente a Sthaphylococcus epidermidis - Marcos Rodríguez, Jesi Fiorela (2018)
The present research work was aimed at determining the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of the hydroethanolic extract of the Persea americana "avocado" seeds against Staphylococcus epidermidis; from the populated center of the district of Moche, province of Trujillo. The hydroetanolic extract of Persea americana seeds was obtained by mashing with constant agitation for 15 days. It also presented the following organoleptic characteristics: dark orange color, suigéneris smell, liquid texture, bitter taste. Then the CMI was determined by the M27-A3 method standardized by the Clinical and Laboratory Standards Institute (CLSI), adapted to the research, ten concentrations were used; and the CMB was performed by the method of agar dilution using the technique of surface planting in Muller-Hinton agar, a value of 12.5% was obtained, for both determinations against Staphylococcus epidermidis